A EFEKTIVITAS DAN KONTRIBUSI RETRIBUSI PELAYANAN PASAR TERHADAP PENERIMAAN RETRIBUSI DAERAH DI KABUPATEN BERAU: EFEKTIVITAS DAN KONTRIBUSI RETRIBUSI PELAYANAN PASAR TERHADAP PENERIMAAN RETRIBUSI DAERAH DI KABUPATEN BERAU - Dandy Ahmad Drajat (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2018)
The purpose of this research is to know the level of effectiveness and contribution of acceptance of Retribution of Market Service to the acceptance of Regional Retribution in Berau District in 2008 until 2014. Analyzer used to test the hypothesis include: Effectiveness Ratio and Contribution Ratio. The results showed that the effectiveness of Market Service Levy collections during 2008 to 2014